Tissue-Specific Effects of Reduced β-catenin Expression on Adenomatous Polyposis Coli Mutation-Instigated Tumorigenesis in Mouse Colon and Ovarian Epithelium. - Ying Feng; Naoya Sakamoto; Rong Wu; Jie-Yu Liu; Alexandra Wiese; Maranne E Green; Megan Green; Aytekin Akyol; Badal C Roy; Yali Zhai; Kathleen R Cho; Eric R Fearon (PLoS Genetics, 2015)
Adenomatous polyposis coli (APC) inactivating mutations are present in most human colorectal cancers and some other cancers. The APC protein regulates the β-catenin protein pool that functions as a co-activator of T cell factor (TCF)-regulated transcription in Wnt pathway signaling. We studied effects of reduced dosage of the Ctnnb1 gene encoding β-catenin in Apc-mutation-induced colon and ovarian mouse tumorigenesis and cell culture models. Concurrent somatic inactivation of one Ctnnb1 allele, dramatically inhibited Apc mutation-induced colon polyposis and greatly extended Apc-mutant mouse survival. Ctnnb1 hemizygous dose markedly inhibited increases in β-catenin levels in the cytoplasm and nucleus following Apc inactivation in colon epithelium, with attenuated expression of key β-catenin/TCF-regulated target genes, including those encoding the EphB2/B3 receptors, the stem cell marker Lgr5, and Myc, leading to maintenance of crypt compartmentalization and restriction of stem and proliferating cells to the crypt base. A critical threshold for β-catenin levels in TCF-regulated transcription was uncovered for Apc mutation-induced effects in colon epithelium, along with evidence of a feed-forward role for β-catenin in Ctnnb1 gene expression and CTNNB1 transcription. The active β-catenin protein pool was highly sensitive to CTNNB1 transcript levels in colon cancer cells. In mouse ovarian endometrioid adenocarcinomas (OEAs) arising from Apc- and Pten-inactivation, while Ctnnb1 hemizygous dose affected β-catenin levels and some β-catenin/TCF target genes, Myc induction was retained and OEAs arose in a fashion akin to that seen with intact Ctnnb1 gene dose. Our findings indicate Ctnnb1 gene dose exerts tissue-specific differences in Apc mutation-instigated tumorigenesis. Differential expression of selected β-catenin/TCF-regulated genes, such as Myc, likely underlies context-dependent effects of Ctnnb1 gene dosage in tumorigenesis.